The impact of sowingdate and production area on the yield of white lupin (Lupinus albus L.) on Nyírség brown forest soil - Tóth, Gabriella; Borbély, Ferenc (Acta Agraria Debreceniensis, 2014)
The lupine is very sensitive to the different ecological conditions. The examinations of lupine was started in 2003 and our aim is determine yield components which directly affecting crop yields (flower, pod and seed number per plants) in different sowing times (3 times, two weeks apart) and growing area area (240, 480, 720 cm2) combinations. According to our results the sowing times, the growing area and the meteorological conditions are influence on yield significantly. Our data suggest that the early sowing and large growing area combination is favourable to rate of fertilized plants and to development of yield. Later sowing reduces the seed yield depending on the cropyear. In our experiment, the decrease of yield was in the unfavourable year (2003) 20–96%, and in the most favourable meteorological conditions (2004) 10–79%, and in rich rainfall year (2005) 15–88%.